ANALISIS FAKTOR-FAKTOR PENYEBAB PEKERJA ANAK DI BAWAH UMUR PADA SEKTOR INFORMAL DI KOTA KUPANG (Studi di Dinas Sosial Kota Kupang) - Maria Carita Bebhe; Umbu T.W. Pariangu; Delila A. Nahak Seran (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
This research aims to analyze the factors causing underage child labor in the informal sector in Kupang City and to analyze the duties and responsibilities of the Kupang City Social Service in overcoming the problem of underage child labor. This research is qualitative research with data collection techniques, namely interviews, observation and documentation. The informants in this research were working minors, parents, the community, and parties from the Kupang City Social Service. The results of this research reveal that economic, cultural, social environmental factors and the desires of the children themselves cause young children to enter the world of work to fulfill their needs. The weak economy in the family greatly influences welfare so that it is not only parents who work but children also take part in the world of work. The Kupang City Social Service as a regional government institution also plays a role in their duties and responsibilities regarding social welfare for street children who work as minors, such as the rehabilitation program, namely returning children to their families so that they no longer work on the streets, carrying out supervision and monitoring, raids, and the TEPAK program (Child and Family Capacity Strengthening Meeting).